Avaliação da expressão dos genes PTAFR E PF-4 como potenciais biomarcadores moleculares plaquetários de estratificação de risco na Covid-19 - Sales, Lívia de Oliveira (2023)
Even in the face of vaccination programs and the significant decline in serious cases of the disease, COVID-19 challenges us in different aspects. SARS-CoV-2 infection presents different severity levels, which suggests the influence of genetic factors on the clinical outcome of these patients. In cases of severe COVID-19, different studies have described the presence of elevated coagulation markers, increased platelet activation and aggregation, and a significant risk of thrombotic complications. And, given the participation of these cells in several viral infections and their negative action when associated with a pro-thrombotic response, understanding the mechanistic role of SARS-CoV-2 with platelets appears to be a promising path. The expression of Platelet Activating Factor (PAF) and Platelet Factor 4 (PF-4) in different viral infections, such as dengue, were associated with the appearance of more severe symptoms of the disease and greater replication of the virus. In this context, this study aimed to evaluate the expression profile of the PTAFR and PF-4 genes in hospitalized patients and demonstrate their correlation with the severe form of COVID-19. To this end, we characterized the expression profile of PTAFR and PF-4 using the real-time PCR technique of 93 patients with COVID-19 in hospital care, in which we demonstrated a hyperexpression of these genes when compared to healthy individuals (p<0,05). However, there was no significant association between their expressions and the clinical-epidemiological parameters addressed (p>0,05). Furthermore, for comparative analysis, we stratified patients according to type of hospitalization, clinical outcome and gender, in relation to age and laboratory tests, where the correlation between age and outcome and gender (p<0,05), count of leukocytes (p<0,001) and platelets (p<0,0001) and International Normalized Ratio (INR) (p<0,05) to clinical outcome, and between CRP values (p<0,05) and D -dimer (DDM) (p<0,05) to the type of hospitalization, were identified as possible markers of clinical prognosis and monitoring of the disease. However, there were no significant correlations between: age, leukometry and INR and type of hospitalization; between CRP and DDM levels at outcome; and leukocyte and platelet counts, CRP, INR and MDD according to gender (p>0.05). Therefore, our results support the hypothesis that increased expressions of PTAFR and PF-4 are associated with a more severe clinical context of the disease, requiring hospital care and may be important predictors of the risk of severe COVID-19.